PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM MULTIKULTURAL BERBASIS OUTCOME BASED EDUCATION (OBE) - Rahmawati, Zuli Dwi; Wahyuni, Sri (TA'LIM : Jurnal Studi Pendidikan Islam, 2024)
Curriculum development in all lines of education shows serious urgency in efforts to provide for the needs of society globally, one of which is multicultural Islamic education which is deliberately collaborated with curriculum design based on outcome based education (OBE) in order to realize multicultural Islamic education that accommodates the diversity of society. Based on the applicable curriculum, the Darul 'Ulum Islamic University PAI study program has three graduate profiles, namely PAI educators, managers and administrators of educational institutions and edupreneurs. The graduate profile becomes a curriculum reference by providing output-based multicultural Islamic education innovations to improve student learning outcomes and work readiness. This research uses a qualitative approach with focus group discussion techniques by policy stakeholders in study programs and curriculum experts. The results of the research show that the development of the OBE-based multicultural Islamic education curriculum in the Darul 'Ulum Islamic University pie study program was carried out by providing educational innovation, namely adding Multicultural Islamic Education courses, perfecting the PEO/TPP formulation in the draft curriculum point 3, perfecting the profile of graduates in the curriculum draft point 3, perfecting learning outcomes in the PLO 8 code with the affective domain and organizing the Multicultural Islamic Education course as a compulsory study program subject which is an integral part of the curriculum.